2006
DOI: 10.1021/cm0618805
|View full text |Cite
|
Sign up to set email alerts
|

Simple Route to Gradient Concentric Metal and Metal Oxide Rings

Abstract: Gradient concentric rings with unprecedented regularity, formed by drying a polymer solution from a sphere-on-Si geometry, are utilized as templates for preparing a wide variety of metal or metal oxide rings. This simple yet novel approach affords a cost-effective means to produce metal or metal oxide rings in a concentric fashion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
44
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 23 publications
0
44
0
1
Order By: Relevance
“…The axially symmetric sphere-on-flat geometry provides a unique environment (i.e., a bound solution) for controlling the flow within an evaporating droplet, which in turn regulates the structure formation. [35][36][37][38][39][40][41] Thus, in sharp contrast to the irregular concentric rings formed due to stochastic ''stick-slip'' cycles of the contact line when a droplet evaporates from a single surface (i.e., an unbound solution), [44,45,47,48] highly ordered, gradient concentric rings of MEH-PPV are produced using the sphere-on-flat geometry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The axially symmetric sphere-on-flat geometry provides a unique environment (i.e., a bound solution) for controlling the flow within an evaporating droplet, which in turn regulates the structure formation. [35][36][37][38][39][40][41] Thus, in sharp contrast to the irregular concentric rings formed due to stochastic ''stick-slip'' cycles of the contact line when a droplet evaporates from a single surface (i.e., an unbound solution), [44,45,47,48] highly ordered, gradient concentric rings of MEH-PPV are produced using the sphere-on-flat geometry.…”
Section: Resultsmentioning
confidence: 99%
“…[35][36][37][38][39][40][41][42][43] Rather than allowing the solvent to evaporate over the entire droplet area as in copious past work, in which droplets evaporated from a single surface, [44][45][46] the evaporation was restricted at the droplet edges. [35,36] Concentric rings were formed by controlled, repetitive pinning and depinning of the contact line (i.e., ''stick-slip'' motion).…”
Section: Introductionmentioning
confidence: 99%
“…20 As depicted in Figure 2c, PMMA rings were formed at the surface of Au-coated ITO. The sample was then treated with the KI/I 2 DI water solution to selectively dissolve Au between PMMA rings.…”
mentioning
confidence: 90%
“…Hence, the ability to precisely control the capillary flow and convective flux in drying‐mediated self‐assembly to create spatially well‐defined surface structures has received considerable attention. To date, a few elegant studies have demonstrated intriguing means based on the controlled evaporation in confined geometries (i.e., bound solution) to delicately tailor the evaporative self‐organization process, thereby yielding highly ordered structures 4–23. For example, by rationally designing the upper curved surface in curve‐on‐flat geometries to accommodate different shapes, a wide range of complex surface patterns with unprecedented regularity were readily produced during the course of solvent evaporation by controlled, repetitive pinning–depinning cycles of the three‐phase contact line of the droplet constrained in curve‐on‐flat geometries 24.…”
mentioning
confidence: 99%